2023
DOI: 10.1007/s10346-022-02020-4
|View full text |Cite
|
Sign up to set email alerts
|

Land use and land cover as a conditioning factor in landslide susceptibility: a literature review

Abstract: Landslide occurrence has become increasingly influenced by human activities. Accordingly, changing land use and land cover (LULC) is an important conditioning factor in landslide susceptibility models. We present a bibliometric analysis and review of how LULC was explored in the context of landslide susceptibility in 536 scientific articles from 2001 to 2020. The pattern of publications and citations reveals that most articles hardly focus on the relationship between LULC and landslides despite a growing inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…For the land cover parameter, the highest FR values for the use of BNPB and NASA landslide occurrence data are in the secondary mangrove forest and open land classes, which are 2.69 and 5.71, respectively. Vegetation can protect soil from erosion and improve slope stability through mechanical anchoring by vegetation roots [17]. Therefore, land cover in the form of secondary mangrove forest and open land can reduce the level of soil or slope stability, causing landslides.…”
Section: Resultsmentioning
confidence: 99%
“…For the land cover parameter, the highest FR values for the use of BNPB and NASA landslide occurrence data are in the secondary mangrove forest and open land classes, which are 2.69 and 5.71, respectively. Vegetation can protect soil from erosion and improve slope stability through mechanical anchoring by vegetation roots [17]. Therefore, land cover in the form of secondary mangrove forest and open land can reduce the level of soil or slope stability, causing landslides.…”
Section: Resultsmentioning
confidence: 99%
“…The study also seeks to analyse the distribution of landslides in relation to the identified GmD patterns. Rapid land use/cover change (LUCC) and climate change, which is causing shifts in rainfall patterns, are suspected to intensify the risk associated with landslides in the mountainous region (Hao et al, 2022;Mateos et al, 2020;Pacheco Quevedo et al, 2023) Geologically, Meghalaya consists of the Gneissic complex of Archaean to Paleoproterozoic aeon to recent alluvial fills in the intracratonic linear depression of the Meghalayan stage of the Late Cenozoic era Strong et al, 2019). Overall, the majority of the area, $44% (concentrated in the northern and northwestern parts), is covered by an unclassified Gneissic complex with patches of greenstones and sediments of the Shillong group (Mishra, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study also seeks to analyse the distribution of landslides in relation to the identified GmD patterns. Rapid land use/cover change (LUCC) and climate change, which is causing shifts in rainfall patterns, are suspected to intensify the risk associated with landslides in the mountainous region (Hao et al, 2022; Mateos et al, 2020; Pacheco Quevedo et al, 2023). The study further examines the changes in land use land cover (LULC) in Meghalaya, given the region's high susceptibility to landslides and the concurrent growth of tourism‐related activities, rapid urbanization and infrastructure development.…”
Section: Introductionmentioning
confidence: 99%
“…In numerous studies conducted over the past few decades, land use has consistently been considered a significant causative factor in landslide susceptibility. However, despite its recognized importance, the exploration of land use changes in landslide susceptibility analysis has been limited, leaving a significant potential for future research [14]. While, the rapid expansion of urbanization has led to the conversion of substantial areas of forested and cultivable land into urban fringes.…”
Section: Introductionmentioning
confidence: 99%
“…This transformation, combined with the challenging terrain and complex topography, has significantly increased the occurrence of landslides caused by human interventions [15]. Moreover, recognizing the importance of land use in landslide assessment requires examining the influence of human activities on slopes, particularly agricultural and forestry practices [14]. These activities are further influenced by climate change, emphasizing the need for effec tive management strategies to minimize landslide susceptibility [13.…”
Section: Introductionmentioning
confidence: 99%